2014
DOI: 10.1039/c4ta03221g
|View full text |Cite
|
Sign up to set email alerts
|

Uniform nanoparticle coating of cellulose fibers during wet electrospinning

Abstract: This work outlines a newly developed method that allows electrospun cellulose fibers to be coated with nanoparticles during dry-jet wet electrospinning. Fibers coated with Mg(OH)2 nanoparticles exhibited flame retardant properties, whereas fibers containing Mg(OH)2 nanoparticles exhibited accelerated burning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…In this regard, Mg-based NPs are also used to develop promising fireproof clothes. For example, Zheng et al [201] reported the synthesis of nanofibers coated with Mg(OH) 2 NPs by wet electrospinning. They placed the flame-retardant NPs exclusively on the surface of the fibers in order to impact its combustion behavior.…”
Section: Characteristics Synthetic Naturalmentioning
confidence: 99%
“…In this regard, Mg-based NPs are also used to develop promising fireproof clothes. For example, Zheng et al [201] reported the synthesis of nanofibers coated with Mg(OH) 2 NPs by wet electrospinning. They placed the flame-retardant NPs exclusively on the surface of the fibers in order to impact its combustion behavior.…”
Section: Characteristics Synthetic Naturalmentioning
confidence: 99%
“…When a volatile organic solvent is used, solvent evaporation occurs at this stage. Conversely with (non-volatile) IL or OES solvents, 13,14,18,120,121 the solution is discharged into a collection bath (e.g. water 14 or EtOH 122 ), causing precipitation of the polymer fibres.…”
Section: Fibre Electrospinningmentioning
confidence: 99%
“…It is a new trial is to physically immobilize MH on the surface of fiber under swelling without modification of MH and cellulose fiber. There are many researches on the use of ionic liquid (IL) to dissolve and regenerate cellulose [18][19][20][21][22]. However, there are relatively few studies about using IL to swell cellulose for immobilizing inorganic particles to achieve functional fabric.…”
Section: Introductionmentioning
confidence: 99%